Analisa Sistem Pakar Diagnosa Penyakit Influenza (Flu) Pada Orang Dewasa Dengan Metode Forward Chaining - Khairudin; Noviantara, Andhika; Aji Budiman, Luzen; Apriyanti, Wiwi; Rosyani, Perani (CV. Shofanah Media Berkah, 2023)
Expert system is a technology that is widely used in the health sector, one of which is for disease diagnosis. Influenza (Flu) is one of the respiratory diseases caused by a virus called the influenza virus. Diseases caused by climate change are usually Influenza (Flu) and cold diseases, which are often considered the same by society. The purpose of this study was to design an expert system application for the diagnosis of these two different diseases, namely flu and colds. The research data is sourced from data from the Ministry of Health of the Republic of Indonesia (KEMENKES). The design of this expert system application uses the Forward Chaining method with google appsheet and google sheet tools. The results showed that all the features of the application have worked properly after being tested using the black box testing method. This application also helps people be able to distinguish flu and cold diseases, it is shown through the results of an online survey that 91% of respondents need this expert system application.